81.9k views
3 votes
A=3x+7 B=2x^2-1 C=7x^2-3x Find: A+B+C= A-B-C=

User Ron
by
5.2k points

1 Answer

3 votes

Given the equations:


A=3x+7
B=2x^2-1
C=7x^2-3x

• You need to add them in order to find:


A+B+C

Set p that:


A+B+C=(3x+7)+(2x^2-1)+(7x^2-3x)

Remember the Sign Rules for Multiplication:


\begin{gathered} +\cdot+=+ \\ -\cdot-=+ \\ +\cdot-=- \\ -\cdot+=- \end{gathered}

Then, you know that the positive signs between the parentheses do not change the signs inside of them:


A+B+C=3x+7+2x^2-1+7x^2-3x

Combine the like terms (these are defined as those terms that have the same variables with the same exponents). Then:


A+B+C=9x^2+6

• Subtract the equations in order to find:


A-B-C

Set up that:


A-B-C=(3x+7)-(2x^2-1)-(7x^2-3x)

Simplify it by distributing the negative signs and then combining the like terms:


A-B-C=3x+7-2x^2+1-7x^2+3x
A-B-C=-9x^2+6x+8

Hence, the answer is:


A+B+C=9x^2+6
A-B-C=-9x^2+6x+8

User Inigomedina
by
4.3k points